THE ROLE OF THE ENVIRONMENTAL AND FORESTRY SERVICES OF BENGKULU PROVINCE IN THE DEVELOPMENT OF LAKE DUSUNBAR NATURAL TOURISM PARK - Ahmad Jamil; Titi Darmi (Yayasan Wayan Marwan Pulungan, 2023)
The role of the government in preserving the Danau Dusun Besar Nature Tourism Park is crucial through the issuance of regulations, legal protection, funding, supervision, public education, and international cooperation to create sustainability and fairness and involve community participation. The park’s management includes providing infrastructure, empowering the local community, and ensuring the safety and security of visitors. As a result, Lake Dusun Besar Nature Tourism Park in Bengkulu City can be promoted as an iconic destination, a source of Regional Original Revenue, and recognized as a World Heritage Site by UNESCO.